(untitled) (Zaporizhzhia Historical Review, 2021)
One of the main measures of tsarist government and Synod in the struggle against the Old Belief in the middle of the 19-th century, – the conversion to the Orthodoxy and Edinoverie is analyzed in the article. The author defines the peculiarities of speading the Edinoverie in Chernigov, Kharkov and Poltava guberniyas and also tries to clear up the extent of effectiveness of this governmental measure. The scholar emphasizes the difference in perception of Edinoverie by the official Orthodox Church and the Old Believers themselves.